Information Systems Acquisition Decisions: Learning Management System of SolBridge. Issue 2 (November 2016) - Hameed, Tahir; Swar, Bobby
SolBridge, a young business school in South Korea, acquired an open-source learning management system (LMS) in early years of its operation. It switched to an on-premises proprietary LMS a few years later. However, before renewal of its annual license SolBridge was caught in a typical dilemma of information systems acquisition (IS acquisition), i.e., keeping the costs lowest while maximizing user and organizational benefits. The decision was made more complex by newly available cloud-hosting options. SolBridge CIO analyzed the total cost of ownership (TCO) and benefits of several options before recommending one of them to school management. This case provides senior undergraduate or graduate students with an opportunity to assume the role of SolBridge CIO and analyze TCO for its next LMS. Not only will they realize the managerial challenges involved in selection and acquisition of enterprise information systems but they will also learn about the economic feasibility of on-premises and cloud-hosting options. It also becomes visible to them that organizations grapple with unceasing technological and organizational changes. Therefore, flexibility and scalability emerge as key elements of modern IT infrastructure.